Knowing God and Knowing About God: Martin Buber's Two Types of Faith Revisited - Moberly, R. W. L. (Scottish journal of theology, 2012)
Initially I briefly expound Martin Buber's Two Types of Faith so as to clarify Buber's sharp contrast between Jewish faith (Hebrew Emunah) and Christian belief (Greek Pistis). I suggest that Buber's polarisation of Emunah, a trust and existential engagement with God, over against Pistis, an intellectual acknowledgement which lacks immediacy with God, has certain resonances with Wilfred Cantwell Smith's distinguishing between ‘faith’ and ‘belief’ in his attempt to overcome the Enlightenment tendency to reduce religious faith to propositional belief. I also acknowledge that Buber's conceptually alert and religiously constructive engagement with the Bible in its own way embodies many of the concerns in the current attempts to bring Bible and theology together via ‘theological interpretation’ or ‘a canonical approach’. However, Buber's account of the Old Testament overlooks the presence of the idiom ‘to know that’ (Hebrew yada( ki), which points to the importance of cognitive content in relation to knowing Israel's God. I consider a number of narratives which feature the deuteronomic idiom ‘to know that Yhwh is God’ (or closely comparable formulations) – Elijah on Mount Carmel (1 Kings 18), Rahab (Joshua 2), Naaman (2 Kings 5) and David and Goliath (1 Samuel 17) – and consider the function of ‘knowing that Yhwh is God’ in each passage. By way of conclusion I reflect on the complementarity of ‘knowing God’ and ‘knowing about God’ and the problematic nature of tendencies, represented by Buber, to set these over against each other. I also suggest that there is fruitful work to be done through a comparative and synthetic biblical and theological study of the relationship between the Old Testament concern that people should ‘know that Yhwh is God’ and the New Testament concern that people should ‘believe that Jesus Christ is Lord’.